Historicismo y homenaje al papa Luna desde Escocia: la construcción de la Marble Chapel de Mount Stuart (Isla de Bute) y su inspiración en La Seo de Zaragoza: Historicism and tribute to pope Luna from Scotland at the end of the 19th century: the construction of the marble chapel at Mount Stuart (Isle of Bute) and its inspiration from La Seo of Zaragoza - Juberías Gracia, Guillermo (Artigrama, 2025)
Resumen A finales del siglo XIX, la University of St. Andrews rindió homenaje al papa Luna, el pontífice que otorgó la bula de fundación de su studium generale en 1413. Tras este interés por la figura de Benedicto XIII se encontraba el rector de St. Andrews, lord John Patrick Crichton-Stuart, tercer marqués de Bute, un polifacético aristócrata escocés, poseedor de una de las mayores fortunas del Reino Unido durante el periodo victoriano. En 1895 y 1897 envió a España a Robert Rowand Anderson, arquitecto escocés que había diseñado la residencia de los Bute, Mount Stuart, para buscar información sobre el papa Luna. Como consecuencia de estos viajes por las actuales comunidades de Aragón y Valencia, Anderson trajo a St. Andrews numerosas fotografías y objetos relacionados con el pontífice y, en los años siguientes, construyó una capilla en Mount Stuart en la que incluyó una réplica del cimborrio de la Seo de Zaragoza. A través del presente artículo se aportan datos sobre la recuperación de la memoria del papa Luna en Escocia y sobre la construcción de la capilla de Mount Stuart y se relacionan ambos procesos con el medievalismo de lord Bute y su conversión al catolicismo. Abstract In the late 19th century, the University of St Andrews paid tribute to Pope Luna, the pontiff who issued the bull establishing its studium generale in 1413. This interest in the figure of Benedict XIII was spearheaded by lord John Patrick Crichton-Stuart, the third Marquess of Bute and rector of St Andrews, a multifaceted Scottish aristocrat possessing one of the largest fortunes in the United Kingdom during the Victorian period. In 1895 and 1897, he commissioned Robert Rowand Anderson, the Scottish architect responsible for designing his residence, Mount Stuart, to travel to Spain in search of information pertaining to Pope Luna. As a result of those expeditions through current communities of Aragon and Valencia, Anderson returned to St Andrews with several photographs and artifacts associated with the pontiff. Subsequently, he constructed a chapel at Mount Stuart that featured a replica of the dome from the Seo de Zaragoza. This article elucidates the efforts made to recover Pope Luna’s legacy in Scotland as well as details regarding the construction of the chapel at Mount Stuart, connecting both endeavors to lord Bute’s medievalist interests and his conversion to Catholicism. Key words Third Marquess of Bute; Robert Rowand Anderson; Benedict XIII; Mount Stuart; la Seo; neo-Gothic